Role of immediate early genes in the development of salivary gland organoids in polyisocyanopeptide hydrogels - Schaafsma, Paulien; Kracht, Laura; Baanstra, Mirjam; Jellema-de Bruin, Anne L.; Coppes, Robert P. (Frontiers in Molecular Biosciences, 2023)
Human salivary gland organoids have opened tremendous possibilities for regenerative medicine in patients undergoing radiotherapy for the treatment of head and neck cancer. However, their clinical translation is greatly limited by the current use of Matrigel for organoid derivation and expansion. Here, we envisage that the use of a fully, synthetic hydrogel based on the oligo(-ethylene glycol) functionalized polymer polyisocyanopeptides (PICs) can provide an environment suitable for the generation and expansion of salivary gland organoids (SGOs) after optimization of PIC polymer properties. We demonstrate that PIC hydrogels decorated with the cell-binding peptide RGD allow SGO formation from salivary gland (SG)-derived stem cells. This self-renewal potential is preserved for only 4 passages. It was found that SGOs differentiated prematurely in PIC hydrogels affecting their self-renewal capacity. Similarly, SGOs show decreased expression of immediate early genes (IEGs) after culture in PIC hydrogels. Activation of multiple signalling pathways involved in IEG expression by β-adrenergic agonist isoproterenol, led to increased stem cell self-renewal capacity as measured by organoid forming efficiency (OFE). These results indicate that PIC hydrogels are promising 3D matrices for SGOs, with the option to be used clinically, after further optimization of the hydrogel and culture conditions.